Characterisation of the bacterial biosensor GMG in E‐coli BL21 (DE3). Issue 3 (10th July 2019) - Rajasabhai, Rashmi; Go, Maybelle Kho; Shan, Yew Wen
Abstract : In this work, a gold biosensor has been constructed and characterised in Escherichia coli ( E. coli ). Though gold biosensors have been previously reported, a NOT gate gold biosensing genetic circuit was constructed using an orthogonal inverter system as an alternative to a circuit where output is contingent solely on input. This enables the detection of changes in gold concentration whereby circuit remains OFF in presence of inducer and ON in absence of inducer. The proposed biosensor is an alternative to conventional forms of gold detection such as Inductively Coupled Plasma‐Mass Spectrometry (ICP‐MS). The constructed biosensor is a collection of components – golTSB operon (isolated from Salmonella enterica ), mf ‐Lon protease (isolated from Mesoplasma florum ) and associated ssrA degradation tag with GFP acting as a reporter. The minimum time and concentration required by the biosensor gol‐ mf lon‐GFP (GMG) to achieve the ON output is characterised here using plate reader data derived from a single multi‐stage assay.